Heterojunction crystalline silicon solar cell and preparation method and application thereof

By adopting the Ag/ITO/MoOx/MoSz-QD/SiOy/n-c-Si/SiOy/TiOp/ITO/Ag structure in solar cells, the quantum confining effect of MoSz-QD and the characteristics of MoOx and TiOp layers are used to solve the problem of insufficient performance of TMO selective contact layers, and the rapid migration of carriers and effective blocking of non-selective carriers and hole traps is achieved, which significantly improves the performance of solar cells.

CN119677174APending Publication Date: 2025-03-21GUANGZHOU POWER SUPPLY BUREAU GUANGDONG POWER GRID CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411860546.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

In the prior art, the solar cell performance of the transition metal oxide (TMO) selective contact layer is poor, mainly due to the high interfacial defect state density, large passivation surface recombination rate, and limited barrier ability to non-selective carriers.

Method used

Heterocrystalline silicon solar cells using Ag/ITO/MoOx/MoSz-QD/SiOy/n-c-Si/SiOy/TiOp/ITO/Ag structures are formed by oxidation and corrosion of concentrated nitric acid, and MoSz-QD is embedded thereon, combining MoOx and TiOp layers, and using plasma-enhanced atomic layer deposition and magnetron sputtering processes.

Benefits of technology

By inlaiding MoSz-QD and setting MoOx and TiOp layers, the performance of solar cells is significantly improved, including rapid carrier migration, effective broadening of band gap, non-selective carrier blocking and hole trapping, and the performance of TMO selective contact layer is overcome.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119677174A_ABST
    Figure CN119677174A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of photovoltaics, and particularly relates to a heterojunction crystalline silicon solar cell and a preparation method and application thereof. According to the heterojunction crystalline silicon solar cell provided by the invention, MoSz-QD is embedded in the SiOy layer, molybdenum sulfide (MoSz) has good electrical properties, and rapid migration of carriers is facilitated; meanwhile, the band gap of the MoSz-QD can be broadened to gt; 3.0 eV, so that high Ec is formed on an interface to prevent electron transport, and the blocking effect of non-selective carriers (electrons) can be realized; moOx is deposited on the surface of MoSz-QD, an impurity energy level is formed through defect engineering, and only holes are allowed to utilize traps to assist tunneling to form effective transportation, so that the heterojunction crystalline silicon solar cell provided by the invention is a high-performance heterojunction crystalline silicon solar cell; the technical problem that in the prior art, a solar cell with a transition metal oxide (TMO) selective contact layer is poor can be solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of photovoltaic technology, and in particular relates to a heterogeneous crystalline silicon solar cell and a preparation method and application thereof. Background Art

[0002] Solar cells are a type of semiconductor material that can use sunlight to generate electricity. Research to improve the photoelectric conversion efficiency of solar cells and reduce the cost of power generation is conducive to promoting clean energy and reducing the consumption of fossil energy. Currently, the mainstream products in the photovoltaic field are p-type passivated emitter and back-side crystalline silicon cells, which have achieved a photoelectric conversion efficiency of more than 20% in mass production.

[0003] With the development of photovoltaic power generation technology, the structure of solar cells has evolved from the early back surface field passivation to the structure of front / back dielectric layer passivation and localized opening contact and back localized diffusion structure. Surface passivation has always been the focus of crystalline silicon cell design and optimization, but the above structure still has a highly composite metal-semiconductor contact area, and point contact leads to an increase in carrier transport distance, which is not conducive to improving the performance of solar cells. When passivation contacts are used on both sides of the cell, a solar cell with a carrier selective contact structure can be realized. Hereto-junction with Intrinsic Thin-layer (HJT) heterojunction cells, Triex tunnel heterojunction cells and POLO cells are all typical carrier selective contact structures. Among them, HJT cells use intrinsic amorphous silicon (amorphous silicon, a-Si:H) passivation layer, and Triex cells have a structure similar to HJT, using ultra-thin SiO y (silicon oxide, ~1.5nm) replaces a-Si:H as the passivation layer, and the POLO battery uses an ultra-thin tunneling SiO y / Doped polycrystalline silicon (poly-Si) is used as a selective contact layer.

[0004] However, in the carrier selective contact structure, the a-Si:H passivation layer has poor thermal stability and requires a low-temperature metallization process, which has a high production cost. The bandgap width of a-Si:H and poly-Si is small, and there is parasitic light absorption. The preparation of poly-Si requires a long high-temperature annealing process, which increases the additional production cost. In recent years, MgO, TiO2, MoO x , WO xTransition metal oxides (TMO) selective contact layers such as V2O5 and V2O5 have begun to be used in solar cells, with a theoretical photoelectric conversion efficiency of up to 28.5%. The transition metal oxide (TMO) selective contact layer can be prepared by atomic layer deposition (ALD) or thermal evaporation process, with a wide band gap and less parasitic light absorption, but its actual cell efficiency is still somewhat different from that of HIT cells. This is mainly due to the mismatch between the transition metal oxide (TMO) selective contact layer and the single crystal silicon lattice, the high interface defect state density, and the passivation surface recombination rate greater than 10 cms -1 At the same time, the transition metal oxide (TMO) selective contact layer has limited blocking ability for non-selective carriers, and the carriers at the interface will still form a certain recombination, reducing the battery performance. This means that the performance of solar cells based on the transition metal oxide (TMO) selective contact layer needs to be improved. Summary of the invention

[0005] In view of this, the present application provides a heterogeneous crystalline silicon solar cell and a preparation method and application thereof, which are used to solve the technical problem that solar cells with transition metal oxide (TMO) selective contact layers in the prior art are poor.

[0006] The first aspect of the present application provides a heterogeneous crystalline silicon solar cell, the structure of which is Ag / ITO / MoO x / MoS z -QD / SiO y / nc-Si / SiO y / TiO p / ITO / Ag, 1 <x<3,1<y<2,1<z<2,1<p<1.8。

[0007] Preferably, in the heterogeneous crystalline silicon solar cell, the SiO y The thickness of the layer is 1~2 nm;

[0008] The SiO y MoS embedded on the surface z -The particle size of QD is 1~10nm;

[0009] The MoO x The thickness of the layer is 10~20nm;

[0010] The TiO p The thickness of the layer is 10~20nm.

[0011] Preferably, the MoS z -The particle size of QD is 2~3nm.

[0012] Preferably, the thickness of the ITO layer is 70-80 nm;

[0013] The thickness of the Ag interdigital electrode is 300-500 nm.

[0014] The second aspect of the present application provides a method for preparing a heterogeneous crystalline silicon solar cell, which can prepare a heterogeneous crystalline silicon solar cell as described in the first aspect, and the preparation method comprises the following steps:

[0015] Step S1: Use concentrated nitric acid to oxidize and corrode the single crystal silicon wafer to form SiO y , get SiO y / nc-Si / SiO y ;

[0016] Step S2: using Mo source and S source as precursors, plasma enhanced atomic layer deposition is performed on SiO y / nc-Si / SiO y A surface inlaid with MoS z -QD, MoS z -QD / SiO y / nc-Si / SiO y ;

[0017] Step S3, using Mo source and O source as precursors, plasma enhanced atomic layer deposition on MoS z -QD / SiO y / nc-Si / SiO y MoO is deposited on a surface x layer, and MoO x / MoS z -QD / SiO y / nc-Si / SiO y ;

[0018] Step S4: Using Ti source and O source as precursors, plasma enhanced atomic layer deposition

[0019] MoO x / MoS z -QD / SiO y / nc-Si / SiO y TiO is deposited on a surface p layer, and MoO x / MoS z -QD / SiO y / nc-Si / SiO y / TiO p ;

[0020] Step S5: Using ITO as a target material, magnetron sputtering is performed on MoO x / MoS z -QD / SiO y / nc-Si / SiO y / TiO p ITO was prepared on the two surfaces to obtain ITO / MoO x / MoS z -QD / SiO y / nc-Si / SiO y / TiO p / ITO;

[0021] Step S6: Using Ag as a target, magnetron sputtering is performed on ITO / MoO x / MoS z -QD / SiO y / nc-Si / SiO y / TiO p Ag interdigital electrodes were prepared on the two surfaces of / ITO to obtain Ag / ITO / MoO x / MoS z -QD / SiO y / nc-Si / SiO y / TiO p / ITO / Ag.

[0022] Preferably, in steps S2 to S4, the Mo source used is MoCl5 or [(NtBu)2(NMe)2Mo];

[0023] The S source used was H2S;

[0024] The O source used was H2O;

[0025] The Ti source used was Ti(NMe2)4.

[0026] Preferably, in step S2, during the plasma enhanced atomic layer deposition process, the MoCl5 heating temperature used is 100-200° C., and the power of the RF power supply is 50-100W.

[0027] Preferably, in step S3, during the plasma enhanced atomic layer deposition process, the temperature of MoCl5 heating is 100-200°C, and the temperature of H2O heating is 100-120°C;

[0028] The power of the radio frequency power supply is 50-100W.

[0029] Preferably, in step S4, during the plasma enhanced atomic layer deposition process, the temperature of heating MoCl5 is 100-200°C, and the temperature of heating Ti(NMe2)4 is 200-300°C;

[0030] The power of the radio frequency power supply is 50-100W.

[0031] Preferably, in steps S2 to S4, during the plasma enhanced atomic layer deposition process, the stage temperature used for the plasma enhanced atomic layer deposition is 100 to 150° C., and the background vacuum of the cavity is less than 0.01 Pa.

[0032] Preferably, in steps S5-S6, the sputtering gas pressure of the magnetron sputtering is 0.1-0.3 Pa, and the background vacuum of the cavity is less than 0.01 Pa.

[0033] The third aspect of the present application provides an application of the heterogeneous crystalline silicon solar cell described in the first aspect in the field of power generation.

[0034] A fourth aspect of the present application provides a solar cell assembly, comprising a heterogeneous crystalline silicon solar cell as described in the first aspect connected in series and / or in parallel.

[0035] Compared with the prior art, the heterogeneous crystalline silicon solar cell provided by the present application has at least the following technical effects:

[0036] 1. Ag / ITO / MoO provided in this application x / MoS z -QD / SiO y / nc-Si / SiO y / TiO p / ITO / Ag, MoSz-QD embedded in SiO y In the layer, molybdenum sulfide (MoSz) used has good electrical properties, and its low-dimensional structure allows ballistic transfer, and energy state filling only takes 50fs, which is conducive to the rapid migration of carriers.

[0037] 2. Ag / ITO / MoO provided in this application x / MoS z -QD / SiO y / nc-Si / SiO y / TiO p / ITO / Ag, MoSz-QD embedded in SiO y In the layer, MoSz-QD has a quantum confinement effect, which can effectively expand the band gap. The MoSz-QD band gap can be widened to >3.0 eV, forming a high △E interface. c Preventing electron transport can achieve the blocking effect of non-selective carriers (electrons).

[0038] 3. Ag / ITO / MoO provided in this application x / MoS z -QD / SiO y / nc-Si / SiO y / TiO p / ITO / Ag, MoO deposited on the surface of MoSz-QD x Partial oxidation of the MoSz-QD surface can form a weak p-type material. Since the Mo-O bond forms an impurity energy level below the Fermi level between the MoSz-QD bands, it acts as a hole trap. The impurity energy level formed by defect engineering will only allow holes to use trap-assisted tunneling to form effective transport.

[0039] 4. Ag / ITO / MoO provided in this application x / MoS z -QD / SiO y / nc-Si / SiO y / TiO p / ITO / Ag, using plasma enhanced atomic layer deposition and magnetron sputtering, which makes the deposited film uniform and has a fast growth rate, which is very suitable for large-scale industrial preparation. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0041] Figure 1 A schematic diagram of the structure of a heterogeneous crystalline silicon solar cell provided in Example 1 of the present application;

[0042] Figure 2 In a heterogeneous crystalline silicon solar cell provided in Example 1 of the present application, SiO y MoS on the surface z -Schematic diagram of the size distribution of QDs. DETAILED DESCRIPTION

[0043] The present application provides a heterogeneous crystalline silicon solar cell and a preparation method and application thereof, which are used to solve the technical problem that solar cells with transition metal oxide (TMO) selective contact layers in the prior art are poor.

[0044] The technical solution of the present application will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0045] In view of the poor performance of the current transition metal oxide (TMO) selective contact layer solar cells, the present application provides a heterogeneous crystalline silicon solar cell, the structure of which is as follows Figure 1 As shown, including: Ag / ITO / MoO x / MoS z -QD / SiO y / nc-Si / SiO y / TiO p / ITO / Ag, 1 <x<3,1<y<2,1<z<2,1<p<1.8。

[0046] In the heterogeneous crystalline silicon solar cell provided in the present application, the surface of the single crystal silicon wafer is oxidized and corroded by concentrated nitric acid to form SiO y Layer, SiO y It can achieve good interface passivation and has nano-pinholes, which can make MoSz-QD (quantum dots) embedded in SiO y On the one hand, molybdenum sulfide (MoSz) has good electrical properties, and its low-dimensional structure allows ballistic transfer, and energy state filling takes only 50 fs, which is conducive to the rapid migration of carriers. On the other hand, by embedding MoSz-QD (quantumdots) in SiO y The MoS formed in the layer z -QD / SiO y / nc-Si / SiO y In the experiment, MoSz-QD has a quantum confinement effect, which can effectively expand the band gap. The band gap of MoSz-QD can be expanded to >3.0 eV, which makes the interface form a high △E c Blocking electron transport can achieve non-selective carrier (electron) blocking effect, with less parasitic light absorption and high thermal stability; and partial oxidation of the MoSz-QD surface can form a weak p-type material, because the Mo-O bond forms an impurity energy level below the Fermi level between the MoSz-QD bands, it acts as a hole trap, and the impurity energy level formed by reasonable defect engineering will only allow holes to use trap-assisted tunneling to form effective transport; thus, the heterogeneous crystalline silicon solar cell provided by the present application is through SiOy, MoSz-QD and MoO xThe setting of the structure can significantly improve the performance of heterogeneous crystalline silicon solar cells, thereby overcoming the poor defects of current solar cells with transition metal oxide (TMO) selective contact layers.

[0047] As a preferred technical solution, for heterogeneous crystalline silicon solar cells, SiO y MoS embedded on the surface z -QD particle size, such as Figure 2 As shown, the particle size distribution is about 1~10nm; while SiO y The thickness of the layer is 1~2 nm, MoO x The thickness of the layer is 10~20nm, TiO p The thickness of the layer is 10~20nm, MoS z -The particle size of QD is 2~3nm, the thickness of ITO layer is 70~80nm, and the thickness of Ag interdigital electrode is 300~500nm.

[0048] The heterogeneous crystalline silicon solar cell provided in the present application will be specifically described below in conjunction with a method for preparing a heterogeneous crystalline silicon solar cell.

[0049] Example 1

[0050] Embodiment 1 of the present application provides a method for preparing a heterogeneous crystalline silicon solar cell, the preparation method comprising the following steps:

[0051] The double-sided polished single crystal silicon wafer (n-type, resistivity 0.5-5.0Ω.cm, thickness 0.15-0.3mm) is cleaned by a standard RCA cleaning process, and then repeatedly rinsed with deionized water and dried with nitrogen gas for later use to obtain a single crystal silicon wafer;

[0052] The single crystal silicon wafer is oxidized by high temperature concentrated nitric acid for 5 minutes to form extremely thin nano-SiO y Thin layer, SiO y / nc-Si / SiO y , SiO y The layer thickness is about 1~2 nm;

[0053] SiO y / nc-Si / SiO y The sample was fixed on the stage in the PEALD chamber. The stage temperature was 100-150°C. The background vacuum of the chamber was better than 0.01Pa. H2O and H2S heated at 100-120°C were introduced. MoCl5 solution heated at 100-200°C and carried by argon was turned on. The RF power was turned on with a power of 50-100W. Plasma was generated under the excitation of the RF voltage. Then a reaction occurred. The reactant MoSz-QD was embedded in the SiOy Thin layer surface; get MoS z -QD / SiO y / nc-Si / SiO y , MoSz-QD particle size is 1~10nm;

[0054] The reaction source H2S is turned off, and the argon gas carries the reaction source H2O into the RF chamber. The RF power is turned on with a power of 50-100W. Plasma is generated under the excitation of the RF voltage, and then a reaction occurs to form the reactant MoO x Deposited on MoSz-QDs to obtain MoO x / MoS z -QD / SiO y / nc-Si / SiO y ,MoO x The layer is 10~20 nm;

[0055] MoS z -QD / SiO y / nc-Si / SiO y Flip it over, introduce H2O, and let the Ti(NMe2)4 solution heated at 200~300℃ carried by argon enter the RF chamber. Turn on the RF power supply with a power of 50~100W. Under the excitation of the RF voltage, plasma is generated, and then a reaction occurs to form the reactant TiO p Deposited on SiO y layer, MoO x / MoS z -QD / SiO y / nc-Si / SiO y / TiO p , TiO p The layer thickness is 10-20 nm;

[0056] Using ITO target as target material, magnetron sputtering was used to deposit MoO x Layer with TiO p ITO conductive thin layers were prepared on the layers to obtain ITO / MoO x / MoS z -QD / SiO y / nc-Si / SiO y / TiO p / ITO, the thickness of the ITO layer is 70~80nm. During the magnetron sputtering process, the background vacuum of the sputtering chamber is better than 0.01Pa, the sputtering pressure is 0.1~0.3Pa, and the deposition temperature is room temperature;

[0057] Taking Ag target as target material, magnetron sputtering method and interdigital mask are adopted to prepare Ag interdigital electrodes on the ITO conductive layer on two surfaces respectively. The thickness of Ag interdigital electrodes is 300~500nm. During the magnetron sputtering process, the background vacuum of the sputtering chamber is better than 0.01Pa, the sputtering gas pressure is 0.1~0.3 Pa, and the deposition temperature is room temperature.

[0058] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, a person skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some or all of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A heterogeneous crystalline silicon solar cell, characterized in that: The structure is Ag / ITO / MoO x / MoS z -QD / SiO y / nc-Si / SiO y / TiO p / ITO / Ag, 1 <x<3,1<y<2,1<z<2,1<p<1.8。 2. A heterogeneous crystalline silicon solar cell according to claim 1, characterized in that: In the heterogeneous crystalline silicon solar cell, the SiO y The thickness of the layer is 1~2 nm; The SiO y MoS embedded on the surface z -The particle size of QD is 1~10nm; The MoO x The thickness of the layer is 10~20nm; The TiO p The thickness of the layer is 10~20nm.

3. A method for preparing a heterogeneous crystalline silicon solar cell according to any one of claims 1 to 2, characterized in that: The following steps are involved: Step S1: Use concentrated nitric acid to oxidize and corrode the single crystal silicon wafer to form SiO y layer, to obtain SiO y / nc-Si / SiO y ; Step S2: using Mo source and S source as precursors, plasma enhanced atomic layer deposition is performed on SiO y / nc-Si / SiO y A surface inlaid with MoS z -QD, MoS z -QD / SiO y / nc-Si / SiO y ; Step S3, using Mo source and O source as precursors, plasma enhanced atomic layer deposition on MoS z -QD / SiO y / nc-Si / SiO y MoO is deposited on a surface x layer, MoO x / MoS z -QD / SiO y / nc-Si / SiO y ; Step S4: using Ti source and O source as precursors, plasma enhanced atomic layer deposition is performed on MoO x / MoS z -QD / SiO y / nc-Si / SiO y TiO is deposited on a surface p layer, MoO x / MoS z -QD / SiO y / nc-Si / SiO y / TiO p ; Step S5: Using ITO as a target material, magnetron sputtering is performed on MoO x / MoS z -QD / SiO y / nc-Si / SiO y / TiO p ITO was prepared on the two surfaces to obtain ITO / MoO x / MoS z -QD / SiO y / nc-Si / SiO y / TiO p / ITO; Step S6: Using Ag as a target, magnetron sputtering is performed on ITO / MoO x / MoS z -QD / SiO y / nc-Si / SiO y / TiO p Ag interdigital electrodes were prepared on the two surfaces of / ITO to obtain Ag / ITO / MoO x / MoS z -QD / SiO y / nc-Si / SiO y / TiO p / ITO / Ag.

4. The method for preparing a heterogeneous crystalline silicon solar cell according to claim 3, characterized in that: In steps S2 to S4, the Mo source used is MoCl5 or [(NtBu)2(NMe)2Mo]; The S source used was H2S; The O source used was H2O; The Ti source used was Ti(NMe2)4.

5. The method for preparing a heterogeneous crystalline silicon solar cell according to claim 4, characterized in that: In step S2, during the plasma enhanced atomic layer deposition process, the temperature of MoCl5 heating is 100-200°C, and the power of the radio frequency power supply is 50-100W.

6. The method for preparing a heterogeneous crystalline silicon solar cell according to claim 4, characterized in that: In step S3, during the plasma enhanced atomic layer deposition process, the temperature of MoCl5 heating is 100-200°C, the temperature of H2O heating is 100-120°C, and the power of the RF power supply is 50-100W.

7. The method for preparing a heterogeneous crystalline silicon solar cell according to claim 4, characterized in that: In step S4, during the plasma enhanced atomic layer deposition process, the heating temperature of MoCl5 is 100~200℃, the heating temperature of Ti(NMe2)4 is 200~300℃, and the power of the RF power supply is 50~100W.

8. The method for preparing a heterogeneous crystalline silicon solar cell according to claim 3, characterized in that: In steps S5-S6, the sputtering gas pressure of the magnetron sputtering is 0.1-0.3 Pa, and the background vacuum of the cavity is less than 0.01 Pa.

9. Application of a heterogeneous crystalline silicon solar cell according to any one of claims 1 to 2 in the field of power generation.

10. A solar cell module, characterized in that: A heterogeneous crystalline silicon solar cell comprising any one of claims 1 to 2 connected in series and / or in parallel.

Citation Information

Cited By

  • PEDOT: PSS / n-Si solar cell with work function gradient regulated and controlled by doping Mo compound and preparation method of PEDOT: PSS / n-Si solar cell

    CN121358095A